PERHITUNGAN TEBAL PERKERASAN DAN METODE PELAKSANAAN PERKERASAN KAKU PADA PEMBANGUNAN JALAN TOL GEMPOL â PASURUAN - , ERLITA VITANTI PUTRI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Economic and industrial growth in Indonesia accelerate the growth of traffic volume, so that adequate transportation facilities needed to support the smooth running of traffic. This is the basis for the construction of Toll Road Gempol - Pasuruan is expected to boost the economy and support the accessibility of transportation services in the area of Pasuruan. The purpose of pavement thickness design to determine the effective thickness efficient but fulfills the comfort of road users and analyzes the implementation method of rigid pavement in the field refers to the basic guidelines for the implementation of rigid pavement. Methods of implementation rigid pavement on the construction of rigid pavement on Toll Road Gempol - Pasuruan using Slipform Paver slip references. Calculations based on standard guidelines for pavement thickness design of concrete pavement. In this project a layer of concrete pavement slab used rigid pavement thickness 31 cm and the results of the analysis of the implementation rigid pavement work in the field is in conformity with the basic theory and guidelines for the implementation of rigid pavement